Pengaruh Penyuluhan Kesehatan tentang Bahaya Pergaulan Bebas terhadap Pengetahuan pada Remaja - Wiwik Widiyati; Ratna Sari Rumakey (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Promiscuity is a form of deviant behavior that crosses the boundaries of obligations, demands, rules, conditions and feelings. If this interaction and experimentation is without limits, teenagers can be dragged into negative or promiscuous relationships. Teenagers who fall into promiscuity are usually due to their lack of knowledge about the dangers and impacts of promiscuity both on their health and their future. The aim is to find out the effect of health education. about the dangers of promiscuity on knowledge among teenagers at SMA Negeri 2 Buru. This type of research is quantitative pre-experiment with the design used is one group pretest-posttest design. The sampling technique is purposive sampling technique. Data analysis using the Wilcoxon test. The results of this research showed that there was an increase in knowledge after being given health education about the dangers of promiscuity on knowledge among teenagers at SMA Negeri 2 Buru p-value = 0.000, where the α value <0.05. This shows that Ho was rejected and Ha was accepted, which means there is an influence of health education about the dangers of promiscuity on the knowledge of teenagers at SMA Negeri 2 Buru. Based on the research results, it shows that there is an influence of health education about the dangers of promiscuity on knowledge among teenagers at SMA Negeri 2 Buru with a p value = 0.000